Greetings from Spinalonga! The Island of Silence in social photo and the culture of memory on Instagram - Nowak, Tomasz Łukasz (Poznańskie Studia Slawistyczne, 2023)
In modern narratives, the island of Spinalonga appears an attractive tourist destination with an interesting and enigmatic history. In fact, Spinalonga is a memory space, encumbered with past political decisions and medical negligence. This is the story of the great confinement, the isolation of the sick who were symbolically killed. Meanwhile, the photos shared on Instagram show the island in a completely different light. The article seeks to answer the following questions: Does the behavior of Instagram users disrupt the culture of memory and how do these photos (digital representations of memory) influence the image of the island? To this end, I outline the history of the island in the context of exclusion mechanisms for those with Hansen's disease. I discuss the issues of dark tourism, social photo and desemantization of communication. I juxtapose the whole thing with the examples of photos from Spinalonga published on Instagram in 2022.